From de-anglicization to internationalisation: cultural representations of the uk and the usa in global, adapted and local elt textbooks in argentina (2006)
It is generally acknowledged that the culture of English-speaking countries has abandoned its central role in recent ELT materials. However, this study suggests that representations of the Anglo-American culture are still favoured in ELT textbooks but that, in most cases, they have been transformed into “international” attitudes. This idea is tested by the compilation of lists of cultural references for four series of textbooks in use in Argentina, and by the application of the procedures of Critical Discourse Analysis (CDA) to a selection of reading passages from them. The findings provide an answer as to what representations of English-speaking cultures are in current textbooks and open to debate the apparent fairness of English as an International Language (EIL). Key words: Cultural representations, culture of English-speaking countries, materials design, English as an international language, critical discourse analysis Existe un consenso casi generalizado en que la cultura de los países de habla inglesa ha abandonado su papel central en los textos de inglés como lengua extranjera. Sin embargo, se sugiere que las representaciones de la cultura Anglo-americana aun persisten sólo que transformadas en actitudes “internacionales”. Esta idea se pone a prueba mediante la compilación de listas de referencias culturales en cuatros series de libros en uso en Argentina y en el Análisis Crítico del Discurso (ACD) de una serie de textos destinados a la lectura en dichos volúmenes. Los resultados determinan qué representaciones culturales subsisten en los textos y abren al debate la aparente neutralidad del inglés como lengua internacional (EIL, por sus siglas en inglés). Palabras claves: Representaciones culturales, cultura de los países de habla inglesa, diseño de materiales, inglés como lengua internacional, análisis crítico del discurso